Ч. 2: Химические свойства - Антонова М. М. Майя Максимовна; Брахнова И. Т. Ирина Тихоновна; Борисова А. Л. Алла Лукинична; Дворина Л. А. Людмила Андреевна; Дроздова С. В. Светлана Валентиновна (1976, 1976)
Авт. указ. на обороте тит. л.